Study on Creativity Potential of Scheduled Cast Students With Ref to Reliability of Language Creativity: Exploring the Creative Potential of Scheduled Caste Students Using Socio-economic and Demographic Variables (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Thepresent investigation addresses itself to the exploration of the creativepotential of scheduled caste students based upon diverse socio-economicparameters and selected demographic variables. The study will be conducted bytaking primary data as a base. However it will be supplemented with theavailable secondary data .The details of the methodology to be adopted in thepresent study will be as under: